The study of Health Literacy of adults in Karaj - Mahdi Sahrayi; Rahman Panahi; Seyedeh-somayeh Kazemi; Zahra Goli Rostami; Heshmatollah Rezaie; Reza Jorvand (Mashhad University of Medical Sciences, 2017)
Background and objective: Health literacy represents the cognitive and social skills that determine the motivation and ability of individuals to acquire, access and understand the information to maintain and promote health. This study aimed to assess the health literacy of adults in Karaj. Methods: In this cross-sectional and descriptive study, 525 subjects aged 18-65 years old were selected using multistage sampling in Karaj. Relevant information was obtained using demographic questionnaire and HELIA questionnaire (18-65 years-old), respectively. Data were analyzed using SPSS and appropriate tests. Results: The mean age of participants was 33.48 ± 11.39 years old. 48.8% (n=250) the participants were male and 51.2% (n=262) were female. 24.2% (n=124) of the participants had inadequate health literacy, 23.4 % (n=120) not so inadequate health literacy, 37.9 % (n=194) adequate health literacy and 14.5 (n = 74) had higher health literacy. Health literacy was significantly associated with age, gender, marital status, education, BMI, smoking and physical activity (p<0.05). Conclusion: Due to low health literacy and the importance of adult role in society, it is necessary educational programs aimed at improving their health literacy skills , designed and implemented. Paper Type: Research Article.